Réponses

2014-01-16T21:39:24+01:00
Bonsoir
1)
9(x+1)² = 4(2x+3)²
 9(x+1)² - 4(2x+3)² = 0    est de la forme de a²-b² = (a-b)(a+b)
[ 3(x+1)-2(2x+3)] [ 3(x+1)+2(2x+3) ] =0
(3x+3 -4x-6)(3x+3+4x+6) = 0
(-x-3)(7x+9) = 0      produit de facteurs donc
soit -x-3 = 0  pour x = 3     soit   7x+9 = 0  pour x = -9/7 
2)
(x+2)/(3x-1) = (x+2)/(x-2) 
(x+2)(x-2) = (x+2)(3x-1) 
(x+2)(x-2) - (x+2)(3x-1) = 0
(x+2)( x-2-3x+1) = 0 
(x+2)(-2x-1) = 0 
soit  x+2 = 0  pour x = -2    ou   -2x-1 = 0   pour x = -1/2
3)
(2x-5)^4 =16              ( ^ veut dire puissance )
(2x-5)^4 - 16 = 0 
(2x-5)^4 - 2^4 = 0
[ 2x-5)² ]² - [2²)² =0 
(2x-5)² - 2² = 0 
(2x-5-2)(2x-5+2) = 0 
(2x-7)(2x-3) = 0  
soit  2x-7 = 0  pour x = 7/2     ou  2x-3 = 0   pour x = 3/2 
4) 
x=-1 donc valeur interdite sur R